Religion and gender culture (Eurasian Journal of Religious Studies, 2024)
The main idea of the author in the article is to identify the differences between “man” and “woman” in the context of the concept of “human” through the history of mythology and religion, taking into account the modern technocratic, scientific-theoretical, service-oriented worldview. In the author`s view, human being is depicted as a man only. In gender language studies, the idea of "humanity" is seen as a general concept, and what is specific is different when we look at "masculinity" and "femininity". Being either relative, or in content, or general and private, a human being – that is idea, used in symbolic approach as masculine and feminine,- is a manifestation form of the gender linguistic. From this point of view, whenever thought we express about a human being, it is linked to its existence and relativity. Author notes that the position of sexes in the society depended on state ideology as well as on the religion at different stages of social development. Analyzing the interpersonal relations of men and women within the framework of Muslim Sharia, the author comes to the conclusion.Key words: religion, gender, Zoroastrianism, Judaism, Christianity, dogmas.